Sistem Pemantauan EKG dan Detak Jantung Berbasis WEB - Rokhim, Ismail; Aminah , Siti; Abdussyakur, Muhammad Shobir (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2022)
The electrocardiogram (ECG) and heart rate are parameters used in the analysis and cardiac activity. Monitoring and analysis is currently still being carried out face-to-face. In this study used the Internet of Things (IOT) and the web-based interface, This is done so that the process of monitoring and analysis of ECG waveforms can be done anywhere and anytime by medical personnel. This study is a continuation of monitoring ECG and heart rate, an AD8232 modul were used to read and conduct bio-voltage signal conditioning from the body with the help of the electrodes. The electrode tapping technique is determined based on Einthoven's triangle theory. In addition, the NodeMCU microcontroller is used to control output and allows running an Internet of Things (IoT) system. Also performed EKG wave output testing, the success rate of data transmission, the realization of the interface as well as testing the accuracy and precision of heart rate values. The results showed that the resulting ECG waves had a frequency of 40Hz and a QRS complex wave period of 0.10 second. In addition, the percentage of success rate of data transmission is 98.84%. Also obtained a heart rate measurement accuracy of 97.966% and a precision level of 0.658%. An interface has also been realized that can display ECG waves in the order of milliseconds and milliseconds.